FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rachmi Astuti (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2020)
The purpose of this study was to determine the effect of liquidity, investmentopportunities, profitability, leverage, and company size on dividend policy in manufacturingcompanies listed on the Indonesia Stock Exchange. The research method uses panel data regressionanalysis method. The unit analysis in this study uses a secondary data source, namely data from thefinancial statements of companies listed on the Indonesia Stock Exchange. The data used arefinancial reports who work in the manufacturing industry during the 2014-2018 period. The resultsshowed that the variables of profitability, leverage, and company size had an effect on dividendpolicy, while the variables of liquidity and investment opportunities had no effect on dividend policyin manufacturing companies listed on the Indonesia Stock Exchange.